Ataîru: modelo ubíquo para o turismo com busca dinâmica de conteúdo baseado em dispositivos móveis - Souza, Thiago Silva de (Universidade do Vale do Rio dos Sinos, 2016)
The way people do tourism has changed considerably in recent decades. These behavioral changes were influenced, among others, by technological factors, because tourists now have several tools to support from the moment in which it thinks about doing tourism, during the tour itself, and even after it. Thus, it is expected more of these support tools in the category utility, reliability and quality of service provided. Many studies have been conducted in this direction, several advances have been achieved and currently there are already several tools that meet current demands of tourists in their itineraries. However, most of them do not take into account some important aspects for the tourist really be helped, for example, find tourist information about cities considered small or far from significant tourist sites. What very noticeable in these current tools, even in commercial nature, is that only the large cities are contemplated, high flow of tourists. The other cities, which also have their tourist attractions, are set aside. Another common feature in today's tools is that the guides are pre-generated and delivered many static data to tourists. In architectural model developed in this work, the collection of tourist information happens dynamically, making content web searches in several open knowledge bases and are constantly updated. From there the information is organized and stored in ontology, and finally delivered to the tourist, based on principles of ubiquitous computing. This ability to search the web makes a larger number of cities can be found and can reach a good level of tourist satisfaction in using the tool as well as increases the perception of the degree of usefulness of the proposed architecture. Therefore, the objective of this work is to develop a system architecture model for the ubiquitous tourism, based mobile devices, called Ataîru, which in the indigenous language Tupi-Guarani means "traveling companion". The model takes into account data on the location and tourist profile, as well as weather data, date and time of the searched location, to provide personalized answers to tourists. To evaluate the proposed model, we used three techniques relevant, namely: evaluation of scenarios, performance evaluation and evaluation of usability. In performance evaluation proved the viability of the model by testing done in the cloud computing environment. In evaluating usability volunteered invited to use the mobile client application Ataîru, where the objective was to evaluate (1) perceived ease of use and (2) application utility perception, and (3) perceived usefulness of the information presented, increasing percentage of total concordance of 72.5%, 82.5% and 67.5%, respectively, and partial concordance 27.5%, 15% and 30%, respectively. This shows that the model supplies the need of tourist of tourist information about cities considered small or far from significant tourist sites, both in quantitative and qualitative aspect.
Keywords: Computação ubíqua; Turismo ubíquo; Agregação de contextos; Busca dinâmica; Personalização de conteúdo; Ubiquitous computation; Ubiquitous tourism; Context aggregation; Dynamic search; Content personalization; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação